2017
DOI: 10.1038/srep41089
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics analyses reveal metabolic alterations regulated by hepatitis B virus core protein in hepatocellular carcinoma cells

Abstract: Chronic hepatitis B virus (HBV) infection is partly responsible for hepatitis, fatty liver disease and hepatocellular carcinoma (HCC). HBV core protein (HBc), encoded by the HBV genome, may play a significant role in HBV life cycle. However, the function of HBc in the occurrence and development of liver disease is still unclear. To investigate the underlying mechanisms, HBc-transfected HCC cells were characterized by multi-omics analyses. Combining proteomics and metabolomics analyses, our results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 52 publications
1
55
0
1
Order By: Relevance
“…Furthermore, autocrine expression of TGF-β is responsible for differences in the stem and migratory phenotype of HCC cells 13 , 14 . Although several clues suggest that metabolic reprogramming may be a transcriptional hallmark in the process to liver carcinogenesis 6 – 8 , 15 , there is still no explanation for the heterogeneity of metabolic profiles found among the different HCC phenotypes, nor the metabolic adaptations of HCC cells to support their migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, autocrine expression of TGF-β is responsible for differences in the stem and migratory phenotype of HCC cells 13 , 14 . Although several clues suggest that metabolic reprogramming may be a transcriptional hallmark in the process to liver carcinogenesis 6 – 8 , 15 , there is still no explanation for the heterogeneity of metabolic profiles found among the different HCC phenotypes, nor the metabolic adaptations of HCC cells to support their migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study indicated that glycolysis and amino acid metabolism had a closely association with the development and progression of HCC by multi-omics analyses [28,29]. Moreover, abnormal lipid metabolism has also been found in HCC patients [30].…”
Section: Discussionmentioning
confidence: 99%
“…Proteomics and metabolomics studies indicate that HBV core protein (HBc) significantly induces glycolysis in HCC cells. It may recruit Max-like protein X (MLX), a transcription factor, and facilitate its translocation to the nucleus, where it promotes the expression of glycolytic enzymes, such as aldolase C (ALDOC) and phosphoenolpyruvate carboxykinase (PCK1) 68 .…”
Section: Modulation Of Glucose Metabolic Signalingmentioning
confidence: 99%